One-hour serum xylose as an absorption test in the tropics. Issue 2 (February 1981) - Hill, P G; Ross, I N; Jacob, R; Jyotheeswaran, S; Mathan, V I
Abstract : The 1-hour serum xylose (surface area corrected) as an indication of xylose absorption after 5 g oral D-xylose has been compared with the 5-hour urine excretion test in a tropical population. The study confirmed that the peak serum xylose concentration occurs at 1 hour and that correction to a constant body surface are improves the discrimination between subjects with normal and impaired xylose absorption. The significantly lower reference range for the 1-hour surface area corrected serum xylose (0.55-1.11 mmol/l) compared to the UK figure reflects the reduced absorptive capacity of the jejunum, a result of tropical enteropathy. In view of the difficulties in obtaining accurate urine collections in tropical countries, especially in field studies, it is recommended that the 1-hour serum xylose (surface area corrected) should be adopted as the standard test of xylose absorption.